1998
DOI: 10.1128/jvi.72.9.7237-7244.1998
|View full text |Cite
|
Sign up to set email alerts
|

Purified, Soluble Recombinant Mouse Hepatitis Virus Receptor, Bgp1b, and Bgp2 Murine Coronavirus Receptors Differ in Mouse Hepatitis Virus Binding and Neutralizing Activities

Abstract: Mouse hepatitis virus receptor (MHVR) is a murine biliary glycoprotein (Bgp1a). Purified, soluble MHVR expressed from a recombinant vaccinia virus neutralized the infectivity of the A59 strain of mouse hepatitis virus (MHV-A59) in a concentration-dependent manner. Several anchored murine Bgps in addition to MHVR can also function as MHV-A59 receptors when expressed at high levels in nonmurine cells. To investigate the interactions of these alternative MHVR glycoproteins with MHV, we expressed and purified to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 66 publications
4
59
0
Order By: Relevance
“…This difference could be accounted for by the difference in virus-binding ability between MHVR1 and MHVR2. The former has more than at least 100-fold higher binding ability than the latter, as examined by virus overlay protein blot assay and neutralization tests using soluble forms of these MHV receptors (Ohtsuka et al, 1996;Zelus et al, 1998). Tight binding of MHV to the receptor could compensate for the combination undesirable for efficient entry into cells found in srr7 S protein.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be accounted for by the difference in virus-binding ability between MHVR1 and MHVR2. The former has more than at least 100-fold higher binding ability than the latter, as examined by virus overlay protein blot assay and neutralization tests using soluble forms of these MHV receptors (Ohtsuka et al, 1996;Zelus et al, 1998). Tight binding of MHV to the receptor could compensate for the combination undesirable for efficient entry into cells found in srr7 S protein.…”
Section: Discussionmentioning
confidence: 99%
“…The neutralization of the mutant viruses by soluble mCEACAM1a [1,4] at 37 jC suggested that soluble mCEA-CAM1a bound S1 on the mutant virions and induced an irreversible conformational change in S2-like wild-type MHV-A59 (Gallagher, 1997;Matsuyama and Taguchi, 2002;Zelus et al, 1998Zelus et al, , 2003. To further characterize the interaction between the mutant viruses and mCEACAM1a, we examined the binding of recombinant S proteins to soluble mCEACAM1a [1,4].…”
Section: Interaction Of Recombinant Viruses With Murine Ceacam1amentioning
confidence: 99%
“…(The cDNA library was derived from mice from the outbred CD-1 strain [21] that were apparently heterozygous at the receptor locus.) Although the SJL/J allele acts as an MHV receptor if over-expressed in tissue culture, it fails to bind MHV virions in virus overlay protein blot assays, and the soluble form has fourfold less virus neutralizing activity than the functional allele [25]. This suggests that it is too weak a receptor to function at endogenous levels; in addition, it is not recognized by CC1 [24].…”
Section: The Mhv Spike Glycoprotein Binds the Canonical Receptor Ceacmentioning
confidence: 99%
“…Independent work identified the contiguous six-amino-acid motif at position 38-43 as crucial for MHV binding [33], and it is noteworthy that CEACAM1b has no homology with CEACAM1a at this sequence ( Figure 2). Although the N domain is necessary and sufficient for neutralization and receptor activity [34], a truncated soluble protein containing only the N and A1 domains neutralizes less efficiently than either the two-or four-domain form, which suggests that the fourth Ig-like domain improves MHV binding [25]. The crystal structure of the soluble two-domain protein shows no interaction between the N and A2 domains; however, the critical MHV-binding residues 38-43 are prominently displayed Box 1.…”
Section: The Mhv Spike Glycoprotein Binds the Canonical Receptor Ceacmentioning
confidence: 99%
See 1 more Smart Citation